2019
DOI: 10.1039/c8ew00472b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of fluorescence spectroscopy to monitor contaminants in source waters and water reuse systems

Abstract: It is of ongoing interest to evaluate real-time instruments for monitoring water contaminants for source water control and water reuse system performance applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…They highlighted, however, that instruments LODs could not be determined with accuracy, due to false negative and false positive results, at low concentrations. Also, Wasswa et al (2019) mentioned that in complex environments, the instruments may not measure towards the minimum LOD due to background fluorescence. Although field fluorimeters have lower sensitivity and LOD ranges compared to benchtop spectrofluorimeters, they are still able to detect the same patterns and trends as laboratory instruments (Mladenov et al, 2018).…”
Section: Advances In Sensor Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They highlighted, however, that instruments LODs could not be determined with accuracy, due to false negative and false positive results, at low concentrations. Also, Wasswa et al (2019) mentioned that in complex environments, the instruments may not measure towards the minimum LOD due to background fluorescence. Although field fluorimeters have lower sensitivity and LOD ranges compared to benchtop spectrofluorimeters, they are still able to detect the same patterns and trends as laboratory instruments (Mladenov et al, 2018).…”
Section: Advances In Sensor Developmentmentioning
confidence: 99%
“…high humidity, high quantity of particulate and DOM even in treated wastewater, high susceptibility to biofilm formation on optical surfaces etc.). Moreover, Wasswa et al (2019) found that the LOD of fluorescence sensors increases due to the high background DOM fluorescence in effluents. They showed, in an ex-situ experiment, that pharmaceutical, personal care products and oil contaminants were more difficult to discern in tertiary effluents than in final treated water.…”
Section: Engineered Water Systemsmentioning
confidence: 99%
“…Different methods have been developed to interpret data from fluorescence excitation/emission matrix (EEM) spectroscopy and to track DOM changes, in terms of quality and quantity, in aquatic ecosystems and water treatment facilities (Chen et al, 2003;Coble, 1996;Parlanti et al, 2000). Efforts have been made to monitor various families of OMPs by using the direct fluorescence signal of organic molecules (e.g., polycyclic aromatic hydrocarbons, pesticides, pharmaceuticals, volatile organic compounds) (Carstea et al, 2016;Ferretto et al, 2014) but the high concentrations of bulk DOM in wastewater hinders the direct detection of trace levels of OMPs (Wasswa et al, 2019). EEMs can nevertheless be used as surrogates for the prediction of OMPs removal, for example during primary and secondary wastewater treatment (Sgroi et al, 2017), because OMPs and DOM undergo common elimination mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence and absorbance spectroscopy have been used in a large number of studies to track water quality changes, mainly related to changes in DOC character. [14][15][16][17][18][19] Analysing fluorescence excitation-emission matrices (EEM) is a very powerful tool to quantify subtle changes in DOC character 15,[20][21][22] that may correlate to macroscopic parameters such as molecular weight, 23 but EEMs are dataintensive. Optical indices can also be useful tools to understand DOC dynamics 24 and some can be rapidly obtained with online sensors that measure only restricted wavelengths.…”
Section: Introductionmentioning
confidence: 99%